2016
DOI: 10.1111/nmo.12824
|View full text |Cite
|
Sign up to set email alerts
|

Tracking gastrointestinal transit of solids in aged rats as pharmacological models of chronic dysmotility

Abstract: Key Points• Understanding conditions of gastrointestinal dysmotility and impaired GI-transit requires accurate noninvasive techniques to monitor the precise location of ingested content.• We demonstrate a non-invasive high resolution X-ray imaging technique to track transit of solid material in vivo, under two specific pharmacological treatment conditions.• Our data indicate GI tract region-specific effects of the modulatory drugs on transit of contents.• We provide evidence that loperamide slows stomach empty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 46 publications
3
36
1
Order By: Relevance
“…Data in the literature on the gastric emptying of solid oral dosage forms in rats is contradictory. A number of studies have reported the failure of capsules to empty from the stomach [18,19], albeit other investigations have demonstrated the transit of solid oral dosage forms through the GI tract [13,20,21]. These contradictory findings are difficult to interpret and may be related to a multitude of factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data in the literature on the gastric emptying of solid oral dosage forms in rats is contradictory. A number of studies have reported the failure of capsules to empty from the stomach [18,19], albeit other investigations have demonstrated the transit of solid oral dosage forms through the GI tract [13,20,21]. These contradictory findings are difficult to interpret and may be related to a multitude of factors.…”
Section: Introductionmentioning
confidence: 99%
“…As such, to better understand intestinal transit, non-invasive imaging techniques have been employed to visualise drug delivery systems along the GI tract [20][21][22][23][24]. Techniques such as magnetic resonance imaging (MRI) [25], single-photon emission computed tomography (SPECT) [13] and X-ray imaging [26] have been applied to track the intestinal movement of solid dosage forms following oral administration.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used for measuring GI transit have been described in detail previously by Dalziel et colleagues. [22][23][24]…”
Section: Gi Transit Procedures and Measurementsmentioning
confidence: 99%
“…The gastric emptying or retention of orally-administered dosage forms in rodent models are currently poorly understood and are subject to varying parameters such as: gastric mobility (Dalziel et al 2017), size of dosage form (Dalziel et al 2016), the effect of anaesthesia (Yamashita et al 2011) and potentially pre-or post-prandial states (Mori 1989), to name a few. A study, for example, demonstrated that enteric-coated gelatine size 9 capsules were able to empty from the stomach of a rat between 2 to 8h after administration (Albrecht et al 2006).…”
Section: Resultsmentioning
confidence: 99%